K.H. Noer Alie’s role in Islamic educational system - Bahari, Che Amnah (IIUM Press, 2017)
This book seeks to identify K.H. Noer Alie’s contribution in the field of education during 1956-1990 at Bekasi-Ujung Harapan, particularly in his Pesantren Attaqwa. The primary focus of this book was to recognize and analyze his philosophical foundation of education, objectives, curriculum and its methodology. Five senior teachers of the pesantren who have the opportunity to study, learn and live with K.H Noer Ali were contacted and input gathered from them were expressed in the writing of this book. From the discussion, it is noted that K.H. Noer Alie was a man of multi tasks, talented and unique. With these caliber and leadership style, he was able to gather his people to participate and benefit the educational system that he has modulled for them accordingly. People thus; appreciate his contribution by conferring various honorship to him during and before his lifetime and some roads at Bekasi are attributed to his name as a sign of respect for him.